Perancangan Video Motion Graphic Tentang Perjalanan Sampah Di Kota Malang - Subari Subari; Stefanus Ericko Dewangga; Rina Nurfitri (LPPM STIKI Malang, 2022)
Garbage accumulation is an impact resulting from unprocessed human activities and society’s indifferent nature. If processed properly, the waste can be a promising product that can increase resources in the area. The problem of waste is still a problem in big cities in Indonesia, and Malang is no exception. The city of Malang itself has a lot of waste piles, namely approximately 492.35 tons/day which is transported to TPS (Temporary Disposal Sites) and approximately 464.74 tons/day which is transported to TPA (Final Disposal Sites). This problem must be considered by the people of Malang City, so an interesting approach is needed so that people are interested. The first step to informing this problem is by making a motion graphic video, which covers 3 things, namely why and why garbage has accumulated, a graph of garbage accumulation in Malang City, and solutions to reduce this accumulation. The purpose of making this motion graphic video is to tell the problem of garbage that has accumulated and must be realized by the outside community, especially the people of Malang City. The result of this design is a motion graphic video that will be distributed through on youtube channel. With a motion graphic video about the waste problem in Malang City, people can be more aware and change their habits of not littering.